1991
DOI: 10.1002/art.1780340307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lobenzarit disodium on human endothelial cells. Lobenzarit disodium inhibits proliferative response, HLA–DR antigen expression, and T cell adherence toward endothelial cells

Abstract: The therapeutic action of lobenzarit disodium (CCA) on the function of endothelial cells (EC) isolated from human umbilical cord veins was investigated. CCA suppressed 3H‐thymidine incorporation into EC in a dose‐dependent manner. Significant inhibition was detected at a concentration of 50 μg/ml. The expression of HLA–DR antigen on the surface of EC was increased when EC were cultured with recombinant interferon‐γ (rIFNγ). Treatment of EC with either IFNγ or interleukin‐1 enhanced the adhesion of T cells to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The mechanism of action of disease-modifying anti-rheumatic drugs (DMARDs) can be summarized as follows: (i) inhibition of cytokine activity/production [16][17][18]; (ii) inhibition of adhesion/costimulatory molecule expression [19][20][21]; (iii) alteration of mononuclear cell population [20,21]; (iv) inhibition of cell growth [22][23][24][25]. Our results demonstrated that clarithromycin produced most of these effects on synoviocytes.…”
Section: Discussionmentioning
confidence: 94%
“…The mechanism of action of disease-modifying anti-rheumatic drugs (DMARDs) can be summarized as follows: (i) inhibition of cytokine activity/production [16][17][18]; (ii) inhibition of adhesion/costimulatory molecule expression [19][20][21]; (iii) alteration of mononuclear cell population [20,21]; (iv) inhibition of cell growth [22][23][24][25]. Our results demonstrated that clarithromycin produced most of these effects on synoviocytes.…”
Section: Discussionmentioning
confidence: 94%
“…If the implications of our in vitro findings are correct, then either CCA is a pro-drug or its effects are indirectly due to other important effects on the immune system [44].…”
Section: The Effects On Inflammatory Mediator Productionmentioning
confidence: 89%
“…The results from three separate experiments are expressed as the mean ±s.d. * /*< O' Ol rer.iii.\-T cell adhesion to synovial cells with incubalion time 0 h. described elsewhere [10], Briefly, endothelial cells (2 x lO^/well) were cultured for 24 h in triplicate in fibroncctin-coalcd 96-weII flat-bottomed microlitre plates (tostar. Cambridge, MA) in 200 /i\ of culture medium in the presence of varying concentrations of reagents.…”
Section: Endothelial Cell or Synovial Celt Monotayer Adhesion As\aymentioning
confidence: 99%